Analisis Efektivitas Penerbitan SP2DK dalam Meningkatkan Penerimaan Pajak di KPP Pratama Depok Cimanggis - Yunisha Kurnia Akbar; Nasution, Hafifah; Respati, Dwi Kismayanti (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study aims to analyze the effectiveness of the Request for Explanation of Data and/or Information (SP2DK) in increasing tax revenue at the Tax Service Office (KPP) Pratama Depok Cimanggis for the 2019-2024 period. This research uses a qualitative approach with primary and secondary data. The results of this study indicate that the implementation of SP2DK at KPP Pratama Depok Cimanggis for the last six years has not been effective, with a low contribution to total tax revenue. Various obstacles such as data validity, changes in taxpayer conditions, and uncooperative attitudes are the main obstacles. However, adaptive strategies such as environmental cooperation, payment facilitation, and transferring the process to audit have been implemented to optimize supervision and improve the effectiveness of SP2DK implementation.